Իվան Կալամյան. ջութակի մանկավարժության լեգենդը - Նարեկ Սարգսյան (ՀՀ ԳԱԱ հրատ.)
Иван Галамян является одним из выдаюшихся педагогов в истории скрипичного исполнительского искусства. Он родился в Тебризе, учился сначала в Москве, у К. Мостраса, потом - в Париже, у Л. Капе, а в 1937 году переехал в Нью-Йорк. До конца своих дней И. Галамян преподавал в Музыкальном институте Кёртис в Филадельфии и Джульярдской школе. Осо- бенностью педагогоки Галамяна является его творческое сопоставление русской и французской школ исполнения. Среди выдающихся учеников Галамяна - Майкл Рабин, Ицхак Перлман, Пинхас Цукерман, Кунг Ва Чунг и другие.Ivan Galamian (1903 -1981) is one of the most prominent pedagogues in the entire history of violin. He was born in Tabriz. He studied in Moscow in the class of K. Mostras, in Paris in the class of L. Capet. In 1937 he moved to New York. Galamian taught at the Curtis Institute of Music and Juilliard School till the end. The uniqueness of the Galamian violin pedagogy is that he incorportated aspects of both Russian and French schools of violin technique in his approach. Among his most famous students are Michael Rabin, Itzhak Perlman, Pinchas Zukerman, Kyung-wha Chung and others.
Keywords: Music; Instrumental Techniques